2007
DOI: 10.1002/esp.1486
|View full text |Cite
|
Sign up to set email alerts
|

Erodibility of soil and organic matter: independence of organic matter resistance to interrill erosion

Abstract: The enrichment of organic matter in interrill sediment is well documented; however, the respective roles of soil organic matter (SOM) and interrill erosion processes for the enrichment are unclear. In this study, organic matter content of sediment generated on two silts with almost identical textures, but different organic matter contents and aggregations, was tested. Artificial rainfall was applied to the soils in wet, dry and crusted initial conditions to determine the effects of soil moisture and rainfall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Haregeweyn et al 2008;Boix-Fayos et al 2009), suggesting that mineralization of OC during the erosion processes at the catchment scale is enhanced compared to other spatial scales as suggested in previous works (e.g. Kuhn 2007;Nadeu et al 2010). The mean sediment ER TOC (0.40±0.24) was very low compared to that of other field studies of similar spatial scale under natural conditions, where the ER TOC ranged between 0.8 and 5.6 (e.g.…”
Section: Discussionmentioning
confidence: 54%
“…Haregeweyn et al 2008;Boix-Fayos et al 2009), suggesting that mineralization of OC during the erosion processes at the catchment scale is enhanced compared to other spatial scales as suggested in previous works (e.g. Kuhn 2007;Nadeu et al 2010). The mean sediment ER TOC (0.40±0.24) was very low compared to that of other field studies of similar spatial scale under natural conditions, where the ER TOC ranged between 0.8 and 5.6 (e.g.…”
Section: Discussionmentioning
confidence: 54%
“…The most important systematic error is the assumption that the carbon concentration of sediment is the same as the soil at the source of erosion. Kuhn (2007) reported that sediment from surfi cial erosion can have a carbon enrichment of up to 50%. Although enrichments of this magnitude are unlikely for massmovement erosion, we take a conservative approach and assign a systematic error of +50% and −25% to represent this uncertainty; as well as that associated with change in carbon content of sediment during transport in rivers (this should be small as travel times in New Zealand's steep and generally short rivers are rarely more than several days).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of non-tilled agricultural areas or undisturbed hillslopes are few (Yoo et al, 2006) or incomplete (Ritchie et al, 2004). Field experiments and flume studies also provide the capacity for solid insights under controlled conditions and demonstrate how much more work is needed to understand field processes (Kuhn, 2007;Schiettecatte et al, 2008).…”
Section: Introductionmentioning
confidence: 99%